Students' experiences and perceptions of online collaborative learning in two Kenyan universities - Caroline Kiarie; Benjamin Muindi (University of Johannesburg, 2020)
Modern advancements in technology have diffused into the higher education sector with electronic communication platforms being used for learning in these institutions. While course instructors are utilizing these platforms in Kenyan universities, there is a dearth of evidence on students' experiences and perceptions of online collaborative learning tools. As such, this study sought to establish the experiences and the perceptions students have of one of the tools, namely blogs, as a learning and collaborative tool. A questionnaire with both closed and open-ended questions was administered to 71 students from a public and a private university in the country. The findings indicate that blogging enhanced interaction among fellow students and instructors and encouraged students to research further outside the classroom. However, students also experienced challenges in blogging, such as a lack of adequate infrastructure and slow internet speed. The study recommends that instructors should adopt the use of collaborative learning tools as teaching and learning moves from physical interaction to online platforms. In addition, institutions should mitigate the challenges faced by the students. This is especially so considering that students have a positive perception towards online collaborative learning. Keywords: Online learning, Collaborative learning, Blogging, Students experiences, University teaching and learning How to cite this article: Kiarie, C. & Muindi, B. 2020. Students' experiences and perceptions of online collaborative learning in two Kenyan universities. Scholarship of Teaching and Learning in the South. 4(2): 138-159. https://doi.org/10.36615/sotls.v4i2.130. This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/